Prescription auditing based on World Health Organization (WHO) prescribing indicators: A case of Dilla University referral hospital - Bekele, Nigatu Addisu; Tadesse, Jarsso (Journal of Drug Delivery and Therapeutics, 2018)
Introduction: Rational use of drugs requires that patients receive medications appropriate to their clinical needs, in doses that meet their own individual requirements for an adequate period of time, at the lowest cost to them and their community. The issues of irrational use of medicines is global and that a global approach coordinated by WHO with more vigorous implementation of leadership and evidence based advocacy of rational use of medicine is essential Materials and Methods: Cross-sectional descriptive and quantitative study was conducted at Dilla University Referral Hospital to determine the current prescribing practices. 1440 prescription were selected using systematic random sampling and reviewed retrospectively for a 2-year period from from September 01/2016 to August 31/ 2018 using prescriptions and Prescription registry. Results: The average number of drugs prescribed per prescription was 1.813 ranging from 1 and 6. 1437(99.79%), 1287(89.38%), 1392 (96.67%), 1428 (99.17%) and 0(0%) of the analyzed prescriptions had name of the patient, date, medical record number, age and address of the patients respectively. Antibiotic and injection was prescribed in 842(58.47%) and 94(6.53%) of encounters respectively. The Percentage of drugs prescribed by generic name and from an essential drug list was 85.33% (n=2227) and 97.43% (n=2543), respectively. Of the total 2610 drugs, 2431(93.14%) drugs were actually dispensed. Conclusion: Polypharmacy, percentage of encounters with with injection and percentage of drugs from essential drug list was within acceptable range. The prescribing practice for antibiotics and generic medicines shows significant deviation from WHO. Keywords: Prescription auditing, WHO prescribing indicators, Dilla University Referral Hospital.